Development toward a double focusing isotopic separator for noble gas isotope enrichment. (4th September 2016) - Lavielle, Bernard; Thomas, Bertrand; Gilabert, Eric; Canchel, Gregory; Horlait, Denis; Topin, Sylvain; Pointurier, Fabien; Moulin, Christophe
Abstract : A double focusing sector field mass filter used in Nier–Johnson geometry has been built in order to perform Kr isotope enrichment for 81 Kr and 85 Kr isotopes. The principle consists in implanting Kr + ions accelerated at 7 keV in Al foils after separation using the magnetic sector. A specific ion source has been designed capable of generating high Kr + ion beams (>0.5 μA) to transfer into the collecting Al foils in 3 to 5 h significant fractions of large Kr samples (10 15 to 10 16 atoms) initially introduced in the instrument. Implanted Kr isotopes can be further selectively released from the Al foil by surface ablation using an infrared laser beam. Implantation yields and enrichment factors are measured using a conventional mass spectrometer. Copyright © 2016 John Wiley & Sons, Ltd.